Geniposide Alleviates Oxidative Stress of Mice With Depression-Like Behaviors by Upregulating Six3os1 - Zou, Tianyu; Sugimoto, Kazuo; Zhang, Jielin; Liu, Yongxiu; Zhang, Yiming; Liang, Hao; Jiang, Yinan; Wang, Jing; Duan, Guoxiang; Mei, Cheng (Frontiers in Cell and Developmental Biology, 2020)
Depression is a major cause of disease burden and severely impairs well-being of patients around the globe. Geniposide (GP) has been revealed to play a significant role in depression treatment. Of note, RNA sequencing of this study identified highly expressed long non-coding RNA Six3os1 in response to GP treatment. Thus, we aim to explore how GP affected chronic unpredictable mild stress (CUMS)-induced depression-like behaviors in mice in vivo and in vitro and the downstream molecular mechanism related to Six3os1. The relationship of Six3os1, miR-511-3p and Fezf1 was evaluated by dual-luciferase reporter gene assay, RIP assay, and RNA pulling down assay. Ectopic expression and knockdown experiments were developed in CUMS-induced mice and neurons with or without GP treatment. In vitro experiments and behavioral tests were conducted to examine alteration of CUMS-triggered oxidative stress following different interferences. The experimental data validated that GP treatment resulted in high expression of Six3os1 and Fezf1 and poor expression of miR-511-3p in CUMS-induced neurons. Six3os1 activated the AKT signaling pathway by upregulating miR-511-3p-targeted Fezf1. Either GP treatment or overexpression of Six3os1 or Fezf1 alleviated depression-like behaviors of CUMS-induced mice. GP treatment, miR-511-3p inhibition or overexpression of Six3os1 or Fezf1 not only reduced oxidative stress in CUMS-induced mice and neurons, but also reduced CUMS-induced neuronal apoptosis. Collectively, GP treatment-mediated Six3os1 upregulation ameliorated oxidative stress of mice with depression-like behaviors via the miR-511-3p/Fezf1/AKT axis.